Differences in chemical composition of PM2.5 emissions from traditional versus advanced combustion (semi-gasifier) solid fuel stoves. (October 2019) - Lai, Alexandra; Shan, Ming; Deng, Mengsi; Carter, Ellison; Yang, Xudong; Baumgartner, Jill; Schauer, James
Abstract: A common strategy to improve indoor air quality in households burning coal and biomass is the introduction of advanced combustion solid fuel stoves, which can use existing fuels yet emit fewer pollutants. Chemical composition of PM is affected by numerous combustion parameters, but is often not considered in energy transitions, despite varying toxicity among chemical components. We analyzed PM2.5 emissions from combustion of solid fuels (coal, wood, and straw; whole and pelletized) in a variety of stoves (cookstoves and heating stoves; traditional and semi-gasifier, including forced versus natural draft and fixed versus reciprocating grate). To assess the effects of fuel and stove type on PM2.5 composition, we measured elemental carbon (EC), organic carbon (OC), water-soluble OC, water-soluble inorganic ions (e.g. SO4 2−, Cl −, K + ), and organic molecular markers. PM2.5 emissions from traditional stoves were mostly carbonaceous: 76–90% organic matter (OM), 5–6% EC, and less than 2% inorganic ions. In contrast, semi-gasifier stoves emitted more inorganic PM2.5 : on average, ions comprised 65%, 9% was OM, and 4% was EC. Within the semi-gasifier cookstoves, forced-draft cookstove emissions had lower OM (1–3%) and higher ion concentrations (84–88%) than the natural-draft cookstove (5–14% OM, 30–83% ions). Levoglucosan was detected in PM2.5 from combustion of wood in the traditional cookstove and biomass pellets in the natural-draft semi-gasifier cookstove, but not from wood pellets in the forced-draft semi-gasifier cookstove. Across a range of different fuels and stoves, stove type influenced emitted PM composition more than fuel type, underscoring the impact of combustion conditions on PM chemical composition. Graphical abstract: Image 1 Highlights: PM emitted by traditional heating and cookstoves was mostly OM and EC. Semi-gasifier stove PM emissions were mostly inorganic (ions), with low OM and EC. Forced draft stove emissions had less water-soluble and total OM than natural draft. Reciprocating grate stove emissions had less OM and EC, more ions than fixed grate. Some coal and wood pellet PM emissions had no picene or levoglucosan (respectively).